2018
DOI: 10.36570/jduhs.2018.2.587
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Body Aspiration in Ear, Nose and Throat among Children Under 13 Years of Age

Abstract: Objective: To determine the foreign body aspiration in ear, nose and throat among children under 13 years of age attending tertiary care hospital, Karachi, Pakistan. Methods: This descriptive cross-sectional study was conducted among children under 13 years of age attending Outpatient Department (OPD) or emergency room with history of foreign body aspiration or children among whom foreign body was retrieved during surgery. All information like age, gender, sharpness of foreign body, type of foreign body, requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Studies in the United Kingdom, the USA, Canada and Pakistan revealed that children below the age of 15 years were prone to choking from bones (Chapin et al 2013;Sofos 2014;Dumas 2018). The effects of unintentional consuming of sharp or larger bones goes beyond choking, as some bones can lead to esophagus trauma, and/or sticking, where surgery may be required (Huck and Kyles 2018;Maqsood et al 2018). In general, overcooking of meat and bones may render smaller bones more chewable and less dangerous to the consumer (Jin- Gi et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the United Kingdom, the USA, Canada and Pakistan revealed that children below the age of 15 years were prone to choking from bones (Chapin et al 2013;Sofos 2014;Dumas 2018). The effects of unintentional consuming of sharp or larger bones goes beyond choking, as some bones can lead to esophagus trauma, and/or sticking, where surgery may be required (Huck and Kyles 2018;Maqsood et al 2018). In general, overcooking of meat and bones may render smaller bones more chewable and less dangerous to the consumer (Jin- Gi et al 2019).…”
Section: Introductionmentioning
confidence: 99%